Comparison of in vitro activities of biotransformation enzymes in pig, cattle, goat and sheep - Szotáková, B; Baliharová, V; Lamka, J; Nozinová, E; Wsól, V; Velík, J; Machala, M; Neca, J; Soucek, P; Susová, S; Skálová, L (Research in veterinary science, 2004)
In vitro activities of cytochromes P450 (7-alkyl/aryloxyresorufin dealkyl(aryl)ases, testosterone hydroxylase/oxidase, 6-chlorzoxazone hydroxylase, 7-methoxy-4-trifluoromethyl-coumarin demethylase, and lauric acid hydroxylases), reductases of carbonyl group (toward metyrapone, daunorubicin, glyceraldehyde, and 4-pyridine-carboxaldehyde) and conjugation enzymes (p-nitrophenol-UDP-glucuronosyl transferase, 1-chloro-2,4-dinitrobenzene glutathione-S-tranferase) in young adults, males, non-castrated (N=6) farm animals were studied and compared. Presence of proteins cross-reacting with anti-human CYP3A4, CYP2C9, and CYP2E1 IgG was detected in all farm species. Bovine microsomes differed from other microsomes of farm species in very high 7-ethoxyresorufin-O-deethylase activity (CYP1A1/2). Significantly higher 7-methoxy-4-trifluoromethyl-coumarin demethylase (2-3 times) and 12-lauric acid hydroxylases (4-10 times) activities (probably corresponding to CYP2C and CYP4A, respectively) were found in ovine microsomes. The highest 6beta-testosterone hydroxylase activity, which is usually considered to be a CYP3A activity marker, was found in pig. Reductases of all farm animals display considerable ability to reduce carbonyl group of xenobiotics. Significant differences in level and activity of many biotransformation enzymes tested suggest that extrapolation of pharmacokinetic data obtained in one species to another (even related) could be misleading.
Keywords: systém (enzymů) cytochromů P-450; Sheep; Biotransformation; druhová specificita; Sexual Maturation; kozy; zvířata; Swine; Cytochrome P-450 CYP4A; Cytochrome P-450 Enzyme System; Cattle; Male; Goats; skot; Species Specificity; pohlavní dospělost; biotransformace; Animals; mužské pohlaví; cytochrom P450 CYP4A; prasata; ovce